Fekete-Szegö Inequalities for Starlike Functions with respect to k-Symmetric Points of Complex Order. (19th March 2014) - Aouf, M. K.; El-Ashwah, R. M.; El-Deeb, S. M.
Abstract : Sharp upper bounds ofa 3 - μ a 2 2 for the functionf z = z + ∑ m = 2 ∞ a m z m belonging to certain subclass of starlike functions with respect tok -symmetric points of complex order are obtained. Also, applications of our results to certain functions defined through convolution with a normalized analytic function are given. In particular, Fekete-Szegö inequalities for certain classes of functions defined through fractional derivatives are obtained.